FAKTOR-FAKTOR YANG MEMPENGARUHI KETAHANAN PANGAN RUMAH TANGGA DI KELURAHAN HABARING HURUNG KECAMATAN BUKIT BATU KOTA PALANGKA RAYA - Cindy Aliciafahlia; Maleha; Yuprin, A. D. (Program Studi Agribisnis Jurusan Sosial Ekonomi Pertanian Fakultas Pertanian Universitas Palangka Raya, 2019)
The purpose of this study was to determine the conditions of household food security in the Habaring Hurung Village of Bukit Batu Subdistrict, Palangka Raya City and to find out the factors that affect the food security of farm households in Habaring Hurung Village, Bukit Batu Subdistrict, Palangka Raya City. This research was carried out in the Habaring Hurung Village, Bukit Batu Subdistrict, Palangka Raya City. Location selection (purposive). This research was conducted for 3 (three) months from September to November 2018. The number of samples taken was 40 samples, the method used in determining the sample was simple random sampling technique. Data collected includes primary data and secondary data. The analysis tool used is an indicator of the share of food expenditure, multiple linear regression analysis. The results showed that the conditions of household food security in Habaring Hurung Village were 90% in the criteria of food security. The second objective is to find out the factors that affect household food security in Habaring Hurung Village. It is known that the coefficient of determination is 0.692, meaning 69% of household resilience in Habaring Hurung Village is influenced by income factors, family members, household expenditure, education level and spending on rice. While 31% is influenced by other factors that have not been included in the model used. The results of the F test show that the value of Fcount = 5.307 is greater than Ftable = 2.49 at the confidence level of 95%. So that the factors tested together have a significant effect on the resilience of farm households in the Habaring Hurung Village. Partially the number of family members, household expenditure and rice expenditure have a significant effect on the level of confidence of 95% - 99%. Whereas those that did not significantly affect household food security in the Habaring Hurung village were income and education of mothers.